Det första uppdraget - Larsson, Anders (2007)
This is a 20 points graduation thesis, performed at the Department of Urban and Rural Development at the Swedish University of Agricultural Sciences in Uppsala. The main aim of this thesis is to examine what it is like to combine studying with working and starting your own company. Furthermore, I want to be able to convey this knowledge to others. An important part of being a landscape architect is informing people, and making rather abstract issues tangible.